(untitled) (Berlin, 2005)
This volume of covers two inter-related areas of solid state science. The initial chapters provide a starting point for scientists and engineers wishing to understand the status of colloidal nanoparticles. Semiconductor nanocrystals are discussed as examples of crystalline nanoparticles and silica nanoparticles, which are probably the most popular amorphous nanoparticles, are used to illustrate some general principles associated with such materials.
Keywords: Semiconductor nanocrystals,Silicates,Nanoparticles